Efektifitas Implementasi Manajemen Berbasis Sekolah pada SMA Negeri di Kabupaten Buleleng Tahun 2023 - Sora Dipa, Putu; Yudiatmaja, Fridayana; Suarmanayasa, I Nengah (Universitas Muhammadiyah Surabaya, 2024)
This study aims to determine the effectiveness of the implementation of school-based management (MBS) of public high schools in Buleleng Regency in the aspects of independence, partnership, community participation, transparency, and accountability. This research is a quantitative descriptive research. The subjects of this study were 17 public high schools in Buleleng Regency. The data collection method used was a questionnaire with 5 aspects of MBS implementation. The research instrument was a questionnaire consisting of 128 statements and a Likert scale rating. Data analysis was carried out using quantitative analysis techniques with Glickman's quadrant criteria. The results showed that the implementation of school-based management in public high schools in Buleleng Regency was very effective in 5 aspects of SBM in terms of independence, partnership, community participation, transparency and accountability with the T-score of each aspect being positive (+). Thus, the implementation of MBS at public high schools in Buleleng Regency in 2023 obtained a quality T-score value (+ + + + +) with a very effective category. Therefore, it can be concluded that the effectiveness of the implementation of school-based management at public high schools in Buleleng Regency in 2023 is very effective.